Vegetation Analysis Of Compotition in Pasir Putih Beach and Lhokseudu Coastal Area, Aceh Besar District - Sitta Muhara; Supriatno S; Dewi Andayani; Djufri D; Muhibbuddin M (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Vegetation is a number of plant groups of several types that interact with each other in one place. Vegetation analysis is a way to study the structural arrangement of each type of plant. This research has been carried out from October to November 2020. The purpose of this study was to identify the composition of the vegetation in the White Sand Beach and Lhokseudu Coastal Coast, Aceh Besar District. The method in this study used a survey method with purposive sampling, namely the method used to determine the plot.. Data were analyzed quantitatively and descriptively. The results obtained 31 species of plants with 22 families consisting of 10 species of trees, 13 species of shrubs and 8 types of herbs. The species that has the highest NP value in tree habitus is Dyckia frigida Hook. (43.1%). In bush habitus, the species with the highest NP was Chromolaena odorata L. (26.8%), and in herbaceous habitus Lantana camara L. (36.4%). Keywords: Vegetation Analysis, Habitus, Beach.